Matematika kreatif sebagai upaya peningkatan kompetensi lulusan Program studi Pendidikan matematika - Setiana, Dafid Slamet (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The Asean Economic Community (MEA) has both positive and negative impacts. To address this, the quality of Indonesian Human Resources is needed for competition in the race for jobs. Thus an effort should be made to provide students with a variety of knowledge to improve competence so as to improve the development of the times. In order to produce quality human resources, it also requires a quality education system. One effort that can be done is to increase the competence of the struggle of tertiary institutions. Mathematics education graduates will enter the workforce as educators. The demands of the world of work are very high in competence to have good competence. Complete mathematics consisting of interrelated concepts is not easily conveyed. All the explanations above, to complete the mathematics education that can be obtained through development and to improve competence in accordance with the KKNI, it is necessary to improve the quality of learning. Efforts to improve the quality of learning can be done in various ways, one of the way that can be done by learning mathematics through creative mathematics. Creative mathematics can be interpreted as learning mathematics with a variety of methods and using learning media that is in accordance with the learning material and in accordance with the level of student ability. Thus through creative mathematics learning, it is hoped that it will further enhance learning competence, especially for mathematics education programs.